The Forgery of Magdeburg Rights for Veliuona (the Late Eighteenth Century): Its Copies, the History of the Text, and the Circumstances of Its Creation - Gudmantas, Kęstutis (Senoji Lietuvos literatūra, 2024)
The article focuses on the so-called ‘Privilege of Sigismund the Bearded’, by which Veliuona was allegedly granted Magdeburg rights in 1443 and which defined the boundaries of the lands of the Veliuona church. The article provides an overview of the copies of the forgery created in the late eighteenth century, the historiography, the circumstances of its creation, and its political and socio-cultural context.